Students’ Ability and Factors in Using Subject-Verb Agreement: A Case Study of Indonesian EFL Learners in University Level - Febriyanti, Rina Husnaini (Linguists : Journal of Linguistics and Language Teaching, 2019)
Learning subject-verb agreement (SVA) is still challenging to be mastered by EFL learners especially in University level. Hence, the aim of this study id to describe the student’s ability and to find out the factors in using SVA. The method of this study used qualitative method that displaying analysis descriptively. The participants were 100 Indraprasta PGRI Jakarta University students who took grammar class and learnt about subject-verb agreement. The data was collected by giving test involved short answer choices that consisted of basic SVA, SVA using expression of quantity, SVA using there +be, and SVA using some irregularities, and short multiple-choice questions that related with the factors of learning SVA. The result showed the student’s ability in using SVA in fairly good and the factors came from the student’s motivation in improving their ability such as lack of reading the materials of SVA, lack of understanding on the SVA materials, lack of understanding on their lecturer’s explanation, lack of rereading the SVA materials after getting explanation from their lecturer, lack of doing the exercises, lack of practicing by themselves in SVA exercises, lack of doing self-correction in practicing SVA exercises, lack of doing analysis on the mistakes of SVA exercises, and lack of restudying the mistakes of SVA exercises.